Large Software Implementation Project: A study of software development and project management literature - Väisänen, Maija (My University, 2017)
This study focuses on large scale software delivery, where development is done on top of an existing system or parallel to it. This thesis aims to answer to the question: How to implement a large scale custom solution? Large scale projects take longer than smaller projects to implement and usually they are done in more than in one release. The application’s life-cycle is also planned to last up to decades. Large projects also need special project management skills, executive support, internal investments, strategical vision as well as alignment between IT and business. Large projects are usually complex and have several dependencies. This study also explains what issues projects usually have and what are the constrains of legacy systems and data migration. Different eras of IT systems are also presented as well as reasons why companies should invest to IT solutions. Waterfall model and Agile methodology fundamentals and background are presented shortly. From Agile methodology Scrum and SAFe frameworks are presented as examples. Keywords: Legacy system, Data Migration, Software implementation, project management, COTS, Agile development, Waterfall